Community-based Empowerment: Unveiling patron-client Patterns in Voluntary Trader Partnerships for Enhanced Production in Desa Kolot, Cikalong Tasikmalaya - Prijana, Prijana; Iwan Koswara; Neneng Komariah (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2023)
Enhancing production activities in Desa Kolot, Cikalong Tasikmalaya is achieved through mutually beneficial partnerships among traders, exemplifying a community-driven empowerment model. This approach is introduced as a response to counter the negative perceptions associated with interventionist empowerment strategies implemented by head of village. The objective of this research is to uncover the interconnected pattern involving traders with ample capital collaborating with those lacking financial resources. Employing a qualitative methodology with a phenomenological approach, the data analysis utilizes the patron-client theory. The study identifies the effectiveness of an empowerment model that optimizes the local potential of traditional snack production, deeply rooted in the community’s traditions. The empowerment mechanism is executed through voluntary connections established between major traders providing capital and smaller traders contributing culinary products. Small traders, as beneficiaries, get provision of materials, production tools, and skill enhancements offered by larger traders. Similarly, major traders benefit by gaining access to a market for the product of culinary, thereby expanding their customer base. These personal, voluntary, and tradition-bound relationships reflect dyadic connections characterized by an imbalance, potentially leading to domination and exploitation.